2014
DOI: 10.1371/journal.pone.0113008
|View full text |Cite
|
Sign up to set email alerts
|

Demand for Modern Family Planning among Married Women Living with HIV in Western Ethiopia

Abstract: IntroductionPeople living with HIV (PLHIV) have diverse family planning (FP) needs. Little is reported on FP needs among women living with HIV in Ethiopia. Thus, the objective of the study was to assess the demand for modern FP among married women living with HIV in western Ethiopia.MethodsA facility-based cross-sectional survey was conducted on 401 married women living with HIV selected from Nekemte Referral Hospital and Health Center, Nekemte, Oromia, Ethiopia. Convenience sampling of every other eligible pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 13 publications
4
26
4
Order By: Relevance
“…This is also supported by a study conducted in Dire Dawa, Ethiopia which shows a high unmet need for family planning (36%) among women living with HIV [27]. The finding is comparatively higher than the findings reported from Kenya (20%) [31], Ghana 27.8% [22], Western Ethiopia (15.4%) [36], and Hawassa city Ethiopia (19.1) [37]. This study also indicates that 21.4% of participants ever had an unwanted pregnancy and 12.9% ever had induced abortion.…”
Section: Discussionsupporting
confidence: 68%
“…This is also supported by a study conducted in Dire Dawa, Ethiopia which shows a high unmet need for family planning (36%) among women living with HIV [27]. The finding is comparatively higher than the findings reported from Kenya (20%) [31], Ghana 27.8% [22], Western Ethiopia (15.4%) [36], and Hawassa city Ethiopia (19.1) [37]. This study also indicates that 21.4% of participants ever had an unwanted pregnancy and 12.9% ever had induced abortion.…”
Section: Discussionsupporting
confidence: 68%
“…This finding was higher than the findings in Nekemt 15.4% [23] and Hawasa 19.1% [24]. The possible reasons may be due to behavioral difference, difference in health service provision access and utilization.…”
Section: Discussioncontrasting
confidence: 71%
“…Studies done in different African countries showed that unmet need for family planning was range from Malawi 21.9% to 49% in Nigeria [16][17][18][19][20][21][22]. With regard to Ethiopia studies done in different part of the country showed that the unmet need for family planning among HIV positive women on ART ranges 15.4% in Nekemt, to 24.6% in south Gondar and north wollo [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by study done in Bhutajira and Ethiopia. 21 In rural areas where there is lack of awareness about contraception, mass media and personal testimonials of satisfied users can make family planning methods more acceptable. Where contraception already is widely known, mass-media discussions and individual or group counselling can offer clients accurate information, reassurance, and encouragement.…”
Section: Metmentioning
confidence: 99%